Novatian of Rome and the Culmination of Pre-Nicene Orthodoxy - Papandrea, James Leonard (Eugene, Oregon : Pickwick Publications, 2012)
Novatian of Rome and the Culmination of Pre-Nicene Orthodoxy is an overview of the development of Christology and Trinitarian doctrine, which reached a plateau with Novatian, the third-century priest of Rome. Here James Papandrea offers an enlightening and thorough treatment of the thought, historical context, and theological influences of Novatian. Included are an assessment of the alternative Christologies of the pre-Nicene period, a survey of Novatian's legacy, and concluding comments on the relevance of his theology and ecclesiology for the contemporary church.
Vendor-supplied metadata.
Includes bibliographical references.
Keywords: Novatianus; Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Trinity -- History of doctrines -- Early church, ca. 30-600.; Church history -- Primitive and early church, ca. 30-600.; RELIGION / Christian Theology / Ethics; Electronic books